PANDEMI, NEW NORMAL, DAN LIMINALITAS KEHIDUPAN BERAGAMA DI JAWA TIMUR - Haqqul Yaqin; Feryani Umi Rosyidah; Ali Mursyid Azisi (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
The Covid-19 pandemic affects almost all dimensions of human life, including religious life. As an entity also affected by the pandemic, religious life manifests as part of the social problems and dilemmas in the pandemic era. This article tries to explain the liminal movement of religious life in East Java. The aim is to find some urgent dimensions regarding the practice of religious life in the era of the Covid-19 pandemic. The qualitative approach was chosen as a technique to find several essential aspects in the liminal process. By conducting interviews and being supported by online data categorized thematically, this technique can reinforce views and patterns of religious experience. Interviews were conducted with academics, mosque managers, religious leaders, mosque congregations, and community leaders. The research findings are that as a form of experience in the pandemic era, liminality can transmit ritual practices and cultural codes into new ways of doing and adapting religious life into new everyday habits. Amid an increasingly blurred rationality and demands for survival that continue to whack, people take various ways to resist epidemics and disasters and seek protection with various patterns, including religion.